Tomato Dynamin Related Protein 2A Associates With LeEIX2 and Enhances PRR Mediated Defense by Modulating Receptor Trafficking - Pizarro, Lorena; Leibman-Markus, Meirav; Schuster, Silvia; Bar, Maya; Avni, Adi (Frontiers in Plant Science, 2019)
The endocytic trafficking pathway is employed by the plant to regulate immune responses, and is often targeted by pathogen effectors to promote virulence. The model system of the tomato RLP LeEIX2 and its ligand, the elicitor EIX, employs endocytosis to transmit receptor-mediated signals, with some of the signaling events occurring directly from endosomal compartments. Here, to explore the trafficking mechanism of LeEIX2-mediated immune signaling, we used a proteomic approach to identify LeEIX2-associating proteins. We report the identification of SlDRP2A, a dynamin related protein, as an associating partner for LeEIX2. SlDRP2A localizes at the plasma membrane. Overexpression of SlDRP2A increases the sub-population of LeEIX2 in VHA1a endosomes, and enhances LeEIX2-mediated defense. The effect of SlDRP2A on LeEIX2-induction of plant immunity highlights the importance of endomembrane components and endocytosis in signal propagation during plant immune responses.